Efektivitas Pemanfaatan Chatbot AI sebagai Asisten Pembelajaran dalam Meningkatkan Kemandirian dan Hasil Belajar Siswa Kelas VIII di SMP Negeri 1 Baraka - Sutriana Sutriana; Muhammad Naim; Hasnita Hasnita; Darmawati Taro; Asran Asran; Jamaluddin Hanapi; Zamri Zamri (Jurnal Sultra Elementary School, 2025)
The development of information technology has brought significant changes in the world of education, including the use of Artificial Intelligence (AI) as a learning medium. One implementation is the use of AI chatbots as learning assistants to support student independence and improve learning outcomes. This study aims to analyze the effectiveness of AI chatbots in learning for eighth-grade students at SMP Negeri 1 Baraka. This study used a quasi-experimental method with a single-group pretest-posttest design. The study population was all eighth-grade students with a sample of 32 students selected purposively. The research instruments were learning outcome tests and learning independence questionnaires. Data were analyzed using descriptive statistics and t-tests to see significant improvements in learning outcomes. The results showed that the use of AI chatbots as learning assistants had a positive impact on student learning independence, as seen from the average independence score increasing from 65.3 to 81.7. In addition, student learning outcomes also showed significant improvements, with an average pretest score of 62.5 and a posttest score of 79.4. These findings indicate that AI chatbots can be an effective learning medium to encourage student independent learning and improve academic outcomes. This study recommends the routine integration of AI chatbots into the learning process as a strategy to increase student motivation, independence, and learning outcomes.